Environmental Monitoring of Coastal Waters in Poja Village, Bima Regency: A Scientific Base for Sustainable Marine Resource Management - Dermawan, Awan; Mujib, Abd Saddam (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Coastal waters are essential to both marine ecosystems and the livelihoods of local communities, yet they are increasingly vulnerable to degradation due to anthropogenic activities. This study aims to evaluate the water quality of the coastal waters in Poja Village, Sape District, Bima Regency, to assess the environmental health and the impact of local human activities on marine ecosystems. A descriptive-quantitative approach was employed, with water samples collected from seven locations to analyze physical and chemical parameters, including temperature, pH, salinity, ammonia, nitrite, nitrate, and water visibility. The findings revealed that the water quality remains in a favorable condition, with temperatures ranging from 28.3°C to 30.0°C, pH values between 7.3 and 7.8, and salinity within acceptable standards. Nitrate concentrations were recorded between 5 and 10 ppm, indicating some anthropogenic influence, while ammonia and nitrite were undetectable. In conclusion, the coastal waters of Poja Village exhibit good quality, supporting marine ecosystems and local fishing activities. Regular monitoring is essential to ensure the sustainable management and conservation of marine resources.